1996
DOI: 10.1007/s004660050132
|View full text |Cite
|
Sign up to set email alerts
|

Variable-complexity response surface approximations for wing structural weight in HSCT design

Abstract: VARIABLE-COMPLEXITY RESPONSE SURFACE APPROXIMATIONS FOR WING STRUCTURAL WEIGHT IN HSCT DESIGN by Matthew Douglas Kaufman Committee Chairs: Bernard Grossman and Raphael T. Haftka Aerospace Engineering (Abstract) A procedure for generating and using a polynomial approximation to wing bending material weight of a High Speed Civil Transport (HSCT) is presented. Response surface methodology is used to fit a quadratic polynomial to data gathered from a series of structural optimizations. Several techniques are emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…The second order polynomial models have k = (n+1)(n+2)/2 coefficients for n design variables. Giunta, et al (1994) and Kaufman, et al (1996) found that 1.5k sample points for 5-10 variable problems to 4.5k sample points for 20-30 variable problems are necessary to obtain reasonably accurate second-order polynomial models. Therefore, for large-scale problems, 3k sample points are selected and are referred to as a large sample set.…”
Section: Data Samplingmentioning
confidence: 99%
“…The second order polynomial models have k = (n+1)(n+2)/2 coefficients for n design variables. Giunta, et al (1994) and Kaufman, et al (1996) found that 1.5k sample points for 5-10 variable problems to 4.5k sample points for 20-30 variable problems are necessary to obtain reasonably accurate second-order polynomial models. Therefore, for large-scale problems, 3k sample points are selected and are referred to as a large sample set.…”
Section: Data Samplingmentioning
confidence: 99%
“…10. These coefficients are trained using the method of least squares [9]. That is to say, to construct a RS for input variables of N, at least N c samples should be attained and evaluated.…”
Section: Modelsmentioning
confidence: 99%
“…However, when applying RS to some practical problems, the problem of curse of dimensionality emerges [9]. That is, to maintain good accuracy of approximation, one needs to minimize estimations beyond the domain where analyses were performed.…”
Section: Modelsmentioning
confidence: 99%
“…Another strategy presented by Kaufmann et al . entails the use of low‐fidelity models to reduce the region in the design space, and once this is reduced, a high‐fidelity response surface is constructed over this reduced space.…”
Section: Introductionmentioning
confidence: 99%